1989
DOI: 10.1007/bf00349064
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow purging with mafosfamide ? A critical survey

Abstract: Autologous bone marrow transplantation (ABMT) is increasingly used to consolidate remissions, primarily in hematological disease. Various purging strategies have been developed to minimize the risk of reimplantation of tumor cells with the bone marrow autotransplant. Pharmacological purging with the oxazaphosphorine derivative mafosfamide has been studied extensively, and recent clinical data suggest that purging with mafosfamide may translate into superior remission duration if compared to nonpurged ABMT in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Ex vivo marrow purging with the activated-oxazolphosphorine derivatives 4-hydroxyperoxycyclophosphamide (4HC) and INN mafosfamide (Asta-Z 7557) has been used most extensively after the pioneering Baltimore studies [466]. Mafosfamide is generally considered to be the best agent, and has been analysed in depth [467], also with reference to its differential effects upon normal and leukaemic stem cells [468]. The in-vitro chemosensitivity of leukaemic progenitor cells (AML-CFU) to a combination of mafosfamide lysine (Asta-Z 7654) and etoposide was studied, and it was found that the chemosensitivity of AML-CFU closely mimicked that of normal CFU-GM [469].…”
Section: Pharmacological Purgingmentioning
confidence: 99%
“…Ex vivo marrow purging with the activated-oxazolphosphorine derivatives 4-hydroxyperoxycyclophosphamide (4HC) and INN mafosfamide (Asta-Z 7557) has been used most extensively after the pioneering Baltimore studies [466]. Mafosfamide is generally considered to be the best agent, and has been analysed in depth [467], also with reference to its differential effects upon normal and leukaemic stem cells [468]. The in-vitro chemosensitivity of leukaemic progenitor cells (AML-CFU) to a combination of mafosfamide lysine (Asta-Z 7654) and etoposide was studied, and it was found that the chemosensitivity of AML-CFU closely mimicked that of normal CFU-GM [469].…”
Section: Pharmacological Purgingmentioning
confidence: 99%
“…Some of the present purging modalities under study include the application of pharmacologic agents, e.g. 4-hydroperoxycyclophosphamide, vincristine and mafosfamide (5,8,9). Unfortunately, nonspecific cytotoxicity is a problem with this method.…”
Section: Introductionmentioning
confidence: 99%